2015
DOI: 10.1016/j.jcin.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Sequential Proximal Optimizing Technique Versus Kissing Balloon Inflation Technique in Provisional Bifurcation Stenting

Abstract: In comparison with 5 other techniques, the re-POT sequence significantly optimized the final result of provisional coronary bifurcation stenting, maintaining circular geometry while significantly reducing SB ostium strut obstruction and global strut malapposition. These experimental findings confirm that provisional stenting may be optimized more effectively without KBI using re-POT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
106
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 19 publications
(13 reference statements)
3
106
2
Order By: Relevance
“…Concurrent findings of higher rate of incomplete stent apposition and higher mechanical stress in the proximal MV stent when performing kissing balloon inflation suggested an approach involving sequential single balloon SB dilation and proximal MV postdilation as a simpler and more efficient alternative for provisional stenting of bifurcations . The approach implemented in our study, which involves a consecutive POT—SB dilation—final POT sequence, was first assessed in a comparative assessment of six optimization strategies for provisional stenting in a fractal bifurcation model bench test . Data showed that the sequential optimization strategy, that the authors have named re‐POT, significantly optimized the final result of provisional coronary bifurcation stenting, maintaining circular geometry while significantly reducing SB ostium strut obstruction and global strut malapposition .…”
Section: Discussionmentioning
confidence: 87%
“…Concurrent findings of higher rate of incomplete stent apposition and higher mechanical stress in the proximal MV stent when performing kissing balloon inflation suggested an approach involving sequential single balloon SB dilation and proximal MV postdilation as a simpler and more efficient alternative for provisional stenting of bifurcations . The approach implemented in our study, which involves a consecutive POT—SB dilation—final POT sequence, was first assessed in a comparative assessment of six optimization strategies for provisional stenting in a fractal bifurcation model bench test . Data showed that the sequential optimization strategy, that the authors have named re‐POT, significantly optimized the final result of provisional coronary bifurcation stenting, maintaining circular geometry while significantly reducing SB ostium strut obstruction and global strut malapposition .…”
Section: Discussionmentioning
confidence: 87%
“…MCT, with capability of directly visualizing metal stents, has been broadly adopted in assessment of stent performance ex vivo [8, 9]. However, most of BRSs currently available were made of PLLA that is invisible directly under mCT scanning.…”
Section: Resultsmentioning
confidence: 99%
“…The main finding of this analysis is that 5-year mortality was lower among patients who underwent a simple strategy rather than a complex strategy [17 patients (3.8%) vs. 31 patients (7.0%); P=0.04]. Interestingly, the Kaplan-Meyer curves appear to separate after 2 years Figure 1 Proposed contemporary approach to treatment of severe bifurcation lesion (20). *, typically a large SB (>2.5 mm) supplying a large territory of myocardium with significant ostial disease extending over a long segment into the SB; **, typically a smaller SB (<2.5 mm) with focal involvement of the ostium; ***, presence of important dissection or < TIMI 3 flow in SB.…”
mentioning
confidence: 85%